Abakan 2288 : Kalamity's world of mecha design, part one. - Zampriolo, Luca, ....- (Culver City : Designstudio, 2011)
Kallamity (Luca Zampriolo) creates an imaginary future world dominated by dark undertones where protagonist robots (Hard Doll Machines a.k.a. H.D.M.s) mass-produced from recycled metal are needed in a failing society to secure resources for mankind in order to progress its technology. Kallamity poses the question, "As oil and gas are depleted in the future and inhabitants of Planet Earth continue to grow exponentially, how will a world based on the exploitation of these two natural resources maintain its current technological growth?" and then he precedes to present amazing visuals for the answer in the form of ABAKAN ...